PENDETEKSIAN MANAJEMEN LABA RIIL PADA PERUSAHAAN PUBLIK DI INDONESIA YANG MELAKUKAN RIGHT ISSUE - Yuniatmoko, Irawan (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aims to identify firm’s tendency to execute real activities manipulation through price discounts to temporarily increase sales, overproduction to report lower cost of sold goods, and reduction of discretionary expenses to improve reported margins among firms in right issues offering for 2007-2011 periods, which are registered on the Indonesian Stock Exchange. In this research, earnings management measured by three variables of real activities manipulation. That is real activities manipulation through operating cash flow, real activities manipulation through production cost and real activities manipulation through discretionary expense. This research was conducted by using secondary data from financial reports. First step is by performs regression analysis to find the estimated value of normal and abnormal operating cash flow, production costs and discretionary costs. Then performs descriptive statistics, regression analysis and One-Sample T-Test to test each hypothesis. The results indicate that Indonesian companies who conduct right issues is not indicated manage their earnings from real activities manipulation through operating activity cash flows and not indicated by the production costs and discretionary costs. Keywords : Real activities manipulation, earnings management, Right Issue